Shaping of Peripheral T Cell Responses by Lymphatic Endothelial Cells - Humbert, Marion; Hugues, Stéphanie; Dubrot, Juan (Frontiers in Immunology, 2017)
Lymph node stromal cells (LNSCs) have newly been promoted to the rank of new modulators of T cell responses. The different non-hematopoietic cell subsets in LN were considered for years as a simple scaffold, forming routes and proper environment for antigen-lymphocyte encountering. Though, deeper characterization of those cells has recently clearly shown their impact on both DC and T cell functions. In particular, lymphatic endothelial cells (LECs) control lymphocyte trafficking and homeostasis in lymph nodes (LNs), and limit adaptive immune responses. Therefore, the new role of LECs in shaping immune responses has drawn the attention of immunologists. Striking is the discovery that LECs, among other LNSCs, ectopically express a large range of peripheral tissue antigens (PTAs), and further present PTA-derived peptides through MHC class I (MHC-I) molecules to induce self-reactive CD8+ T cell deletional tolerance. In addition, both steady-state and tumor-associated LECs were described to be capable of exogenous antigen cross-presentation. Whether LECs can similarly impact CD4+ T cell responses through MHC class II (MHC-II) restricted Ag presentation is still a matter of debate. Here we review and discuss our current knowledge on the contribution of Ag-presenting LECs as regulators of peripheral T cell responses in different immunological contexts, including autoimmunity and cancer.